2020
DOI: 10.24251/hicss.2020.499
|View full text |Cite
|
Sign up to set email alerts
|

Why Another Customer Channel? Consumers’ Perceived Benefits and Costs of Voice Commerce

Abstract: Owing to rapidly increasing adoption rates of voice assistants (VAs), integrating voice commerce as a new customer channel is among the top objectives of businesses' current voice initiatives. However, customers are reluctant to use their VAs for shopping; a tendency not explained by extant literature. Therefore, this research aims to understand consumers' perceived benefits and costs when using voice commerce, based on a theoretical framework derived from prior literature and the theory of reasoned action. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
(52 reference statements)
2
26
0
Order By: Relevance
“…The second stream of research focuses on the effect of anthropomorphism on the intention to adopt AIET. For instance, Rzepka et al [25] analyzed the effect of anthropomorphism on the intention to use smart speakers for shopping from a cost-benefit perspective. Moussawi et al [12] explored how anthropomorphism influenced the perceived enjoyment and initial trust in smart speakers, which in turn affected the intention to adopt AIET.…”
Section: Overview Of Research Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stream of research focuses on the effect of anthropomorphism on the intention to adopt AIET. For instance, Rzepka et al [25] analyzed the effect of anthropomorphism on the intention to use smart speakers for shopping from a cost-benefit perspective. Moussawi et al [12] explored how anthropomorphism influenced the perceived enjoyment and initial trust in smart speakers, which in turn affected the intention to adopt AIET.…”
Section: Overview Of Research Trendsmentioning
confidence: 99%
“…The unified theory of acceptance and use of technology (UTAUT) [16,22,26], technology acceptance model (TAM) [12,42], artificially intelligent device use acceptance (AIDUA) model [3], and cognition-motivation-emotion framework [14] were used to understand the effects of anthropomorphism on technology adoption. The theory of reasoned action (TRA) was used to examine the relationship between anthropomorphism and people's AIET usage behaviors [25].…”
Section: Overview Of Technologiesmentioning
confidence: 99%
“…For example, the value created may be seen from the end user or the platform provider [13]. The research in [14] targets the interaction with the user and omits the value creation through interaction with other user groups and network effects within as well as between the user groups.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these many advantages of voice commerce, it is reported that in the United States only 14.1% of those who use smart speaker-based VAs regularly employ them to make purchases [1]. This limited uptake of voice commerce can be attributed to several obstacles: Users experience low interaction quality, limited transparency [3,4], and an uncomfortable feeling when shopping via voice [5]. In addition, several studies have found that one of the most important barriers to the widespread use of voice commerce is a lack of trust [5,6], especially when it comes to trust in the competence and benevolence of VAs [3].…”
Section: Introductionmentioning
confidence: 99%
“…This limited uptake of voice commerce can be attributed to several obstacles: Users experience low interaction quality, limited transparency [3,4], and an uncomfortable feeling when shopping via voice [5]. In addition, several studies have found that one of the most important barriers to the widespread use of voice commerce is a lack of trust [5,6], especially when it comes to trust in the competence and benevolence of VAs [3]. Trust has also been recognized as one of the key success factors for adoption in studies on other information systems (IS) artifacts, particularly in the context of online shopping [7,8].…”
Section: Introductionmentioning
confidence: 99%